MOLECULAR DOCKING OF SELECTED BIOACTIVE COMPOUNDS FROM AZADIRACHTA INDICA FOR THE INHIBITION OF COVID19 PROTEASE - SHARON, S. FEBINA BERNICE (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: COVID-19 caused by novel SARS-coronavirus 2 belonging to family Coronaviridae, is a global public health emergency infecting many people all around the world, especially in India with more than 2,98,000 cases. Hence there is a need for a novel drug that counters SARS-CoV2 is the prime requirement at this time. Methods: The present study aimed to assess bioactive compounds found in Azadirachta indica as a potential inhibitor of COVID-19 Mpr °(6Y2E, 6LU7, and 2GTB) by Autodock 4.2, with the Lamarckian Genetic Algorithm. COVID-19 Mpr ° was docked with thirteen bioactive compounds, and docking was analyzed by Autodock 4.2 and Pymol. Nelfinavir and Saquinavir were used as positive standards for comparison. Results: Azadirachtanin, Azadirachtol, and Salannolide, were left out because of the violation of Lipinski’s rule. The binding energies obtained from the docking of 6Y2E with a native ligand, Azadiradione, Beta-sitosterol, Epiazadiradione, Epoxyazadiradione, Kaempferol, Meldenin, Myricetin, Nimbaflavone, Nimbinene, Nimbione, Nimbocinolide, Quercitrin, Vepnin, Saquinavir, and Nelfinavir were-7.32,-6.63,-6.69,-7.52,-5.27,-4.54,-6.07,-4.19,-5.02,-5.58,-6.23,-4.71, -3.72,-6.4,-7.14 and-4.67 kcal/mol respectively. The binding energies obtained from the docking of 6LU7 with the native ligand, Azadiradione, Nimbione, Vepnin, and Saquinavir were-6.14,-6.48,-6.79 and-6.49 kcal/mol correspondingly. The binding energies obtained from the docking of 2GTB with the native ligand, Azadiradione, Epiazadiradione, Epoxyazadiradione, Kaempferol, Meldenin, Myricetin, Nimbaflavone, Nimbione, Nimbocinolide, Quercitrin, Vepnin, Saquinavir, and Nelfinavir were-6.96,-7.13,-6.69,-5.22,-6.44,-5.06,-5.93,-6.66,-5.3,-5.63,-7.11,-6.89 and-5.42kcal/mol, respectively. Conclusion: Azadiradione, Epiazadiradione, Nimbione, and Vepnin seemed to have the greatest potential to act as COVID-19 protease inhibitors. However, further research is necessary to explore their prospective medicinal use in vitro and in vivo conditions.